Emerging Intestinal Microsporidia Infection in General Population in Jiroft District, Southeastern Iran: A Cross-sectional Study in 2013-2014 - Masoomeh GHADERIPOUR; Khadijeh KHANALIHA; Mehdi MOHEBALI; Saeedeh SHOJAEE; Maryam BARKHORI; Hamed MIRJALALI; Mostafa REZAEIAN (Tehran University of Medical Sciences, 2017)
Background: Microsporidia have been reported as the cause of opportunistic infections in immunocompromised patients in Iran and other countries. There is no data on prevalence of intestinal microsporidia in healthy population of Iran. This study aimed to provide preliminary data on the present status of microsporidia infection in the local healthy population in Jiroft, Kerman Province from southeastern Iran in 2013-2014. Methods: Fresh stool samples were randomly collected from 418 residents in rural 209 (50%) and urban 209 (50%) areas of Jiroft. All of the collected samples were concentrated with conventional formalin-ether, stained with Ryan blue. Microscopic examination was performed with high magnification on each sample separately for the demonstration of microsporidia spores. Results: Microsporidial spores were identified in 41 out of 418 (9.8%) samples including 16.41(39%) from rural areas and 25.41(61%) from urban areas. In general, there was no significant difference between sex, age, job, education, and contact with soil and livestock, water supply, gastrointestinal disorders and microsporidia infection among general population in Jiroft. Conclusion: Intestinal microsporidia infection without clinical manifestations is prevalent in general population resident in southeastern Iran. Appropriate molecular methods are needed for microsporidia species identification.